Discrete Cosine Transform Matrix Based SLM Algorithm for OFDM with Diminished PAPR for M-PSK over Different Subcarriers - Gupta, Prabal; Singh, Rajiv Kumar; Thethi, H. Pal; Singh, Balpreet; Nanda, Santosh Kumar (Journal of Computer Networks and Communications, 2019)
Orthogonal frequency division multiplexing (OFDM) is the highly spectrally well-organized method that has the difficulty of excessive peak power to average power ratio (PAPR), which ultimately imposes constraints on the high-power amplifier. Many practices have been projected to lessen PAPR of the OFDM systems. Amongst all the practices, the selected mapping (SLM) method has drawn more attention because of distortion-less behaviour. This technique uses unique phase sequences. It has been learnt that phase formation for SLM is very tedious. In the proposed work, the SLM method has been used, but phase arrangement formation is based on the usage of discrete cosine transform (DCT) matrix. In this proposed work, discrete cosine transform matrix has been chosen based on the requirement of optimization so that the arrangement with lowest PAPR can be nominated for the transmission. MATLAB simulation depicts that the remarkable gain is achieved as compared with the existing technique. In the proposed work, scheming of phase sequences are very informal due to the use of a DCT matrix which has a definite structure and can be generated at the receiver side with the help of side information of the phases and communicated from the transmitter to the receiver.